Deletion of lrrk2 causes early developmental abnormalities and age-dependent increase of monoamine catabolism in the zebrafish brain. - Stefano Suzzi (Public Library of Science (PLoS), 2021)
LRRK2 gain-of-function is considered a major cause of Parkinson's disease (PD) in humans. However, pathogenicity of LRRK2 loss-of-function in animal models is controversial. Here we show that deletion of the entire zebrafish lrrk2 locus elicits a pleomorphic transient brain phenotype in maternal-zygotic mutant embryos (mzLrrk2). In contrast to lrrk2, the paralog gene lrrk1 is virtually not expressed in the brain of both wild-type and mzLrrk2 fish at different developmental stages. Notably, we found reduced catecholaminergic neurons, the main target of PD, in specific cell populations in the brains of mzLrrk2 larvae, but not adult fish. Strikingly, age-dependent accumulation of monoamine oxidase (MAO)-dependent catabolic signatures within mzLrrk2 brains revealed a previously undescribed interaction between LRRK2 and MAO biological activities. Our results highlight mzLrrk2 zebrafish as a tractable tool to study LRRK2 loss-of-function in vivo, and suggest a link between LRRK2 and MAO, potentially of relevance in the prodromic stages of PD.